Parallel Evaluation of Polyethylene Glycol Conformal Coating and Alginate Microencapsulation as Immunoisolation Strategies for Pancreatic Islet Transplantation - De Toni, Teresa; Stock, Aaron A.; Devaux, Floriane; Gonzalez, Grisell C.; Nunez, Kailyn; Rubanich, Jessica C.; Safley, Susan A.; Weber, Collin J.; Ziebarth, Noel M.; Buchwald, Peter; Tomei, Alice A. (Frontiers in Bioengineering and Biotechnology, 2022)
Pancreatic islet transplantation improves metabolic control and prevents complications in patients with brittle type 1 diabetes (T1D). However, chronic immunosuppression is required to prevent allograft rejection and recurrence of autoimmunity. Islet encapsulation may eliminate the need for immunosuppression. Here, we analyzed in parallel two microencapsulation platforms that provided long-term diabetes reversal in preclinical T1D models, alginate single and double capsules versus polyethylene glycol conformal coating, to identify benefits and weaknesses that could inform the design of future clinical trials with microencapsulated islets. We performed in vitro and in vivo functionality assays with human islets and analyzed the explanted grafts by immunofluorescence. We quantified the size of islets and capsules, measured capsule permeability, and used these data for in silico simulations of islet functionality in COMSOL Multiphysics. We demonstrated that insulin response to glucose stimulation is dependent on capsule size and presence of permselective materials augments delays in insulin secretion. Non-coated and conformally-coated islets could be transplanted into the fat pad of diabetic mice resulting in comparable functionality and metabolic control. Macrophages were found in conformal-coated grafts indicating possible host reactivity. Due to their larger volume, alginate capsules were transplanted in the peritoneal cavity. Despite achieving diabetes reversal, changes in islet composition were found in retrieved capsules and recipient mice experienced hypoglycemia indicative of hyperinsulinemia induced by glucose retention in large capsules as the in silico model predicted. We concluded that minimal capsule size is critical for physiological insulin secretion and anti-inflammatory modulation may be beneficial for small conformal capsules.